Chemical interplay between components in overall thermolysis of CL-20/N2O revealed by ReaxFF molecular dynamics simulations - Chun-xing Ren; Xiao-xia Li; Li Guo (Energetic Materials Frontiers, 2022)
Understanding of the interplay reactions between components in CL-20 bicomponent crystals is fundamental for synthesis and applications of new CL-20 cocrystals and host-guest materials. This paper reports the thermal decomposition of CL-20/N2O host-guest crystal investigated using ReaxFF MD simulations under both isothermal and adiabatic conditions. The isothermal thermolysis simulation at low temperature of 800 ​K and adiabatic decomposition simulation initiated at 800 ​K were performed to reveal as much as the real and overall scenario of CL-20/N2O thermolysis. Two reference systems of ε-CL-20 and CL-20/H2O were employed for clear depiction of reaction mechanism. Permitted by VARxMD for reaction details and facilitated by the three-stage classification, the overall scenario of CL-20/N2O thermolysis and deep insight about the interplay reaction details between host CL-20 and guest N2O were obtained. The dominating of host CL-20 decomposition during entire thermolysis of CL-20/N2O is similar with that of CL-20/HMX and CL-20/TNT. However, the branching ratios of major reaction pathways of CL-20 initial decomposition were altered. The decomposition kinetics in initial thermolysis of CL-20/N2O was found significantly slowed when compared with ε-CL-20, which is caused by the guest N2O molecules that capture the NO2 intermediates generated from host CL-20 decomposition and prevent NO2 from their active participation in further decomposition of the system. It should be noted that the early formation of N2 from guest N2O in CL-20/N2O decomposition accelerates self-heating at certain extent and provides extra oxidative NO3, which slightly compensates to the slowed kinetics in the initial stage. The acceleration effect of guest oxidant N2O on CL-20/N2O decomposition will sustain through the ​oxygen migration of guest N2O in later secondary reactions to form more NOx than that of CL-20/H2O, consequently reducing the reaction zone of CL-20/N2O thermolysis. What was obtained in this work demonstrates that ReaxFF MD simulations combined with the analysis scheme of three-stage classification can facilitate the depiction of thermolysis mechanism of CL-20 bicomponent crystals and be useful in searching for leading candidates of guest molecules for CL-20 host-guest materials.